Photoregulation of lipid metabolism in Begonia: synergistic effects of spectral composition and intensity on stress adaptation - Wang, Zhongke; Fu, Hongbo; Tao, Hongzheng; Ju, Peina; Wei, Hao; Gong, Weichang; Zhuang, Li (Frontiers in Plant Science, 2026)
Light quality and intensity are pivotal environmental cues regulating plant lipid metabolism, yet their combined effects in shade-adapted species remain poorly understood. This study investigates how white (W), red (R), and blue (B) light at intensities of 5, 20, and 50 μmol·m-2·s-1 modulate lipid remodeling in Begonia ‘Black Velvet’. Using integrated lipidomics and transcriptomics, we detected 492 lipid metabolites, with steroids (23.17%) and isoprenes (21.95%) predominating. Principal component analysis revealed that light intensity exerted stronger discriminatory power than spectral quality on global lipid profiles. We annotated 443 differential lipid metabolites (DLMs), including 25 influenced primarily by light quality (e.g., pregnanetriol under blue light) and 23 by light intensity (e.g., glyceroglycolipids peaking at 20 μmol·m-2·s-1). Notably, 409 DLMs showed an interaction between the two factors. Physiological profiling linked key lipids (e.g., chabrolosteroid E, culobophylin C) to antioxidant enzymes (POD, SOD) and oxidative stress markers (MDA). Transcriptomics highlighted regulatory roles for ERG genes in steroid biosynthesis and accD/FabF in fatty acid pathways. Our findings demonstrate an association where Begonia shifts its lipid metabolism in response to light, correlating with adjustments in energy storage, and stress resilience, potentially involving optimization of membrane properties.